Movement to Music - Ivančič, Mirjam (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter highlights the importance of the interaction between music and movement, with a focus on the school environment. It explores the general principles of movement and music from early childhood onwards, the effects of combining them through music and movement activities on children, and insights gained from practical application in primary schools. These discussions are supported by contemporary research across various disciplines, which strongly confirms the positive impact of combining movement and music on children's holistic development—physical-motor, emotional, and cognitive. In addition to demonstrating the effectiveness of integrating music with movement, this chapter emphasizes the key role of teachers in planning and implementing the educational process to support the well-being of children, who will shape and lead our society in the future.